1991
DOI: 10.1136/jcp.44.9.761
|View full text |Cite
|
Sign up to set email alerts
|

Selective location of palisaded myofibroblastoma with amianthoid fibres.

Abstract: The occurrence of a palisaded myofibroblastoma with amianthoid fibres in the left inguinal lymph node of a 51 year old man prompted an investigation of the factors underlying its exclusive location. The antigen profile was characternsed which confirmed the homogeneous expression of vimentin and smooth muscle actin as well as the lack of desmin. Use of monoclonal antibodies to check for a differential distribution of myofibroblasts and the putative cell of origin of palisaded myofibroblastoma showed that inguin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 9 publications
2
29
1
Order By: Relevance
“…Spindle cells of IPM were positive for SMA and vimentin but negative for S-100, Factor-VIII-related antigen, desmin, glial fibrillary acidic protein, epithelial membrane antigen and keratin antibodies [2,7]. Spindle cells were characterized by a continuous expression of actin and vimentin and lack of desmin in all reports in the literature [8]. Our case had also a Inflammatory cell component, lower cellularity similar immune profile.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Spindle cells of IPM were positive for SMA and vimentin but negative for S-100, Factor-VIII-related antigen, desmin, glial fibrillary acidic protein, epithelial membrane antigen and keratin antibodies [2,7]. Spindle cells were characterized by a continuous expression of actin and vimentin and lack of desmin in all reports in the literature [8]. Our case had also a Inflammatory cell component, lower cellularity similar immune profile.…”
Section: Discussionmentioning
confidence: 78%
“…Bigotti et al reported that actin positive/desmin negative myofibroblasts were diffusely prominent in inguinal lymph nodes compared with other lymph node regions. In addition, they suggested that the proliferation of myofibroblasts with this immunophenotype could be secondary to the increased drainage function in inguinal lymph nodes [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schwannoma is quite uncommon in the inguinal region and it is positive for S 100 which differentiates it from IPM. Absence of Ebstein Barr Virus (EBV) DNA, negative immunostaining for HHV 8 and immunocompromised status favors the diagnosis of IPM rather than Kaposi's sarcoma.Also, there are no slit-like vascular channels, extravasated RBCs and no hyaline globules as seen in Kaposi's sarcoma [2][3][4][5][6][7][8][9] . Although the previous studies have provided comprehensive analysis of the characteristic clinicopathologic features of IPM, its pathogenesis remains unknown.…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%
“…IPM was first described in English literature in 1968, although back then it was not classified as IPM. This current name was adopted because of its reflection of a myofibroblastic origin as well as prominent palisaded spindle cells histologically [1][2][3][4][5][6] . It is essential to differentiate IPM from other soft tissue tumors such as Schwannoma, Intranodal leiomyoma, Kaposi's sarcoma, inflammatory pseudotumor, solitary fibromastocytic tumor, angiomyomatous hamartoma and metastatic spindle cell lesions in the lymph node.…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%